PENGARUH INFLASI DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS: PT UNILEVER INDONESIA TBK, PT INDOFOOD SUKSES MAKMUR TBK, DAN PT MAYORA INDAH TBK) - M. Rafli Kurniawan (Universitas Prof.Hazairin,SH Bengkulu, 2026)
Purpose: This study aims to examine the effect of inflation and the Debt to Equity Ratio (DER) on profitability, measured by Return on Assets (ROA), in consumer goods companies listed on the Indonesia Stock Exchange. Methodology/approach: This study applies a quantitative research design utilizing secondary financial data from PT Unilever Indonesia Tbk, PT Indofood Sukses Makmur Tbk, and PT Mayora Indah Tbk for the 2021–2024 period. Multiple linear regression analysis is employed to evaluate both the individual and combined effects of the independent variables on profitability. Results/findings: The results indicate that inflation does not have a significant partial effect on profitability, while DER has a positive and significant effect on ROA. Simultaneously, inflation and DER significantly influence company profitability, with an Adjusted R Square value of 0.524, indicating that 52.4% of the variation in profitability is explained by the model Conclusion: The findings suggest that capital structure, represented by DER, plays a crucial role in enhancing profitability, while macroeconomic conditions such as inflation have a limited direct impact. This study contributes to financial management literature by highlighting the importance of optimal debt management in improving firm performance in the consumer goods sector.